Outcomes, mechanisms and contextual factors of positive psychology interventions for health workers: a systematic review of global evidence - Maartje Kletter; Bronwyn Harris; Celia Brown (BMC, 2021)
Abstract Background Interventions using positive psychology (PP), which build on positive qualities of healthcare personnel and institutions, could potentially enhance organisational performance in healthcare. The aim of this systematic review was to identify if PP interventions have an impact on organisational performance of healthcare personnel, and if so, how this impact can be achieved. We developed a logic model to explain the impact of PP interventions on organisational performance. Methods We searched Web of Science, Medline, Psychinfo, Embase, Scopus and CINAHL (from inception until March 2019) and references of included articles to identify studies that evaluated the impact of a PP intervention for health personnel. Study quality was assessed using the SQUIRE checklist for quality improvement studies. Data were extracted about study details, setting, participants, intervention, method of evaluation and results. Outcomes, mechanisms and contexts were coded in nVivo. Data synthesis was guided by Lewis' theory of the impact of PP interventions on organisational performance and Kneale et al.'s method for logic model development. Collected data were integrated into a logic model explaining initial inputs, processes, and intermediate outcomes of PP interventions that lead to improved organisational performance in healthcare settings. Results We retrieved 4638 articles and identified five through references of included articles of which 29 studies (31 articles) met our inclusion criteria. Most articles were of low quality (n = 19) and outcome measures varied widely. We identified 54 different outcomes of PP interventions, including 'improved well-being' and 'improved interaction and support'. Forty-nine mechanisms were identified including 'recognising and reframing negative interpretations'. Twenty four contextual factors were identified of which seven acted as barriers. 'Managerial support' was a facilitator mentioned in eight studies. All identified outcomes, mechanisms and contextual factors were integrated into a logic model explaining how interventions using PP can impact organisational performance in healthcare. Conclusion Few identified outcomes were statistically significant, however, trends in both quantitative and qualitative outcomes show that PP interventions can increase well-being and interaction and support and thus improve organisational performance in healthcare. The developed logic model can be used in the implementation and evaluation of interventions using PP for health personnel.